A nitroreductase and acidity detecting dual functional ratiometric fluorescent probe for selectively imaging tumor cells. Issue 17 (17th April 2018) - He, Zhaoshuai; Chou, Yajie; Zhou, Hanxin; Zhang, Han; Cheng, Tanyu; Liu, Guohua
Abstract : A dual functional ratiometric fluorescent probe can obviously distinguish acidity, nitroreductase, and nitroreductase in an acidic environment. Confocal fluorescence imaging of A549 cells indicates the probe can detect acidity and expressed nitroreductase in living cells. Abstract : Nitroreductase and acidity are common features of a tumor, which is associated with serious disease with a high mortality rate. However, solo detection of nitroreductase or acidic environments may cause false-positive results. Thus, it is very meaningful to develop dual functional probes for detecting nitroreductase and acidity, as these could be used for accurate tumor imaging. Here we report on the first dual functional ratiometric fluorescent probe, NAFP, for acidity and nitroreductase detection. This probe enables the measurement of the acidic microenvironment and the concentration of nitroreductase at the same time and the same site. The probe can obviously distinguish acidity, nitroreductase, and nitroreductase in an acidic environment. Furthermore, confocal fluorescence imaging of A549 cells indicates thatNAFP can detect acidity and expressed nitroreductase in living cells.